The Genetic Regulation of Aortic Valve Development and Calcific Disease - Menon, Vinal; Lincoln, Joy (Frontiers in Cardiovascular Medicine, 2018)
Heart valves are dynamic, highly organized structures required for unidirectional blood flow through the heart. Over an average lifetime, the valve leaflets or cusps open and close over a billion times, however in over 5 million Americans, leaflet function fails due to biomechanical insufficiency in response to wear-and-tear or pathological stimulus. Calcific aortic valve disease (CAVD) is the most common valve pathology and leads to stiffening of the cusp and narrowing of the aortic orifice leading to stenosis and insufficiency. At the cellular level, CAVD is characterized by valve endothelial cell dysfunction and osteoblast-like differentiation of valve interstitial cells. These processes are associated with dysregulation of several molecular pathways important for valve development including Notch, Sox9, Tgfβ, Bmp, Wnt, as well as additional epigenetic regulators. In this review, we discuss the multifactorial mechanisms that contribute to CAVD pathogenesis and the potential of targeting these for the development of novel, alternative therapeutics beyond surgical intervention.